The impact of alternative development strategies on growth and distribution: simulations with a dynamic model for Egypt - El-Said, Moataz; Lofgren, Hans; Robinson, Sherman (International Food Policy Research Institute, 2001)
Addressing longer-term issues of economic development in Egypt, the paper employs a dynamically recursive computable general equilibrium (CGE) model to assess the outcomes associated with two types of development approaches over the period 1998-2012. One is a targeted sector development approach, and the second is a more broad-based development approach. The results indicate that, when agricultural exports remain relatively low, promoting the Egyptian textile sector is a win-win scenario in terms of rapid growth and equity. In addition, adopting policies that maintain agricultural prices leads to rapid growth and a general improvement of the distribution of income among households. A crucial policy objectives for achieving rapid and egalitarian growth for the Egyptian economy is the ability to secure improved access to international textile markets and the successful expansion of agricultural exports.